2022
DOI: 10.3390/cells11182779
|View full text |Cite
|
Sign up to set email alerts
|

Reforming the Barrier: The Role of Formins in Wound Repair

Abstract: The restoration of an intact epidermal barrier after wound injury is the culmination of a highly complex and exquisitely regulated physiological process involving multiple cells and tissues, overlapping dynamic events and protein synthesis and regulation. Central to this process is the cytoskeleton, a system of intracellular proteins that are instrumental in regulating important processes involved in wound repair including chemotaxis, cytokinesis, proliferation, migration, and phagocytosis. One highly conserve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 124 publications
0
3
0
Order By: Relevance
“…In the case of CR-mediated phagocytosis, actin polymerization is associated with RhoA. This GTPase recruits and stimulates mDia formins [19]; they also activate the Arp2/3 complex.…”
Section: Recognition Of the Target Molecule By The Macrophagementioning
confidence: 99%
“…In the case of CR-mediated phagocytosis, actin polymerization is associated with RhoA. This GTPase recruits and stimulates mDia formins [19]; they also activate the Arp2/3 complex.…”
Section: Recognition Of the Target Molecule By The Macrophagementioning
confidence: 99%
“…Formins promote the initiation and elongation of actin filaments to participate in a variety of biological processes, such as cell signaling, organ development, microtubule stabilization, cell division, and endocytosis. [12][13][14][15] Forminmediated actin assembly is regulated by a protein family consisting of formin-binding proteins (FNBPs/FBPs). Previous studies showed that the high expression of FNBP1 is closely related to the highly aggressive characteristics of tumor cells within gastric and breast cancers.…”
Section: Introductionmentioning
confidence: 99%
“…The RF-EMF is non-ionizing energy at the short-wave radiofrequency band of the electromagnetic spectrum that may be used as a non-invasive therapy delivered through a wound's dressing using small and portable devices that can be self-applied [6]. Researchers found that it may affect nitric Biosensors 2023, 13, 763 2 of 15 oxide signaling, the modulation of cytokine profiles, the expression of growth factors and the regulation of mitogen-activated protein kinase/extracellular signal-regulated kinase, resulting in the wound healing [7].…”
Section: Introductionmentioning
confidence: 99%